The changing role of konowledge professionals as a tool of innovation: theoretical and practical perspectives - Bir, Berat; Erdilek Karabay, Melisa; Yalçınkaya, Bahattin (My University, 2015)
Ad vances and applications in the business environment posed by the digital-age enforce the organizations to renew their strategies and improve their innovative capabilities. Today, the major actors of the knowledge economy are the knowledge professionals. This study aims to provide a comprehensive outlook at the innovation phenomenon within the essential components of Knowledge Management. In this regard, innovation in organizations is discussed within the perspective of knowledge management whereas the importance of knowledge assets in the process of innovation is explained through knowledge professionals. Furthermore, the study contributes to the knowledge management literature by presenting theoretical and practical implications of innovation by examining the latest practices on public services in Turkey.
Keywords: knowledge management; knowledge assets; innovation; knowledge professionals; E-governance